Q11, a CYP2E1 inhibitor, exerts anti-hepatocellular carcinoma effect by inhibiting M2 macrophage polarization - Cunzhen Zhang; Yan Fang; Mengxue Guo; Liming Tang; Yurong Xing; Jun Zhou; Yuanyuan Guo; Yuhan Gu; Qiang Wen; Na Gao; Haiwei Xu; Hailing Qiao (Cancer Immunology, Immunotherapy)
Abstract Despite significant advancements in cancer immunotherapy, many patients continue to respond poorly. Novel therapeutic strategies and drugs are urgently needed. Here, we found that CYP2E1 is upregulated in M2 macrophages. The CYP2E1 inhibitor, Q11, could inhibit M2 macrophage polarization, while CYP2E1 overexpression could promote it. Increased levels of CYP2E1 and M2 macrophages in the tumor microenvironment of HCC patients correlate with poor prognosis. Q11 could inhibit tumor cells by targeting M2 macrophages rather than directly attacking tumor cells. Both Q11 and Cyp2e1 knockout could effectively suppress tumor growth. Q11 reduces the production of CYP2E1 metabolites ( ±)9(10)-DiHOME and ( ±)12(13)-DiHOME, thus attenuating PPARγ activation and M2 macrophage polarization. In summary, our findings suggest that Q11 could suppress M2 macrophage polarization by modulating the CYP2E1/( ±)9(10)-DiHOME or ( ±)12(13)-DiHOME/PPARγ axis, indicating that CYP2E1 may be a potential therapeutic target for HCC, and its inhibitor Q11 may be a potential drug for the treatment of HCC.